Method for Detecting Far-Right Extremist Communities on Social Media; Social Sciences; Vol. 11, iss. 5 - Karpova A. Yu. Anna Yurievna; Savelyev A. O. Aleksey Olegovich; Kuznetsov S. A. Sergey Anatoljeich; Vilnin A. D. Alexander Daniilovich (2022, 2022)
Title screen